Minimal requirements for the molecular testing of lung cancer - Popper, Helmut H.; Tímár, József; Ryska, Ales; Olszewski, Wlodzimierz (Translational Lung Cancer Research; Vol 3, No 5 (October 21, 2014): Translational Lung Cancer Research [The 14th Central European Lung Cancer Congress (CELCC)], 2014)
From the aspect of the contemporary pathologic diagnostics of lung cancer, it is a key issue of the tissue obtained since small biopsies and cytology still play a major role. In the non-small cell lung cancer era, cytology considered equal to biopsy. However, in recent years it is unable to provide quality diagnosis and must be replaced by biopsy. Various molecular techniques can handle various different tissue samples which must be considered during molecular pathology diagnosis. Besides, tumor cell-normal cell ratio in the obtained tissue as well as the absolute tumor cell number have great significance whose information must be provided in the primary lung cancer diagnosis. Last but not least, for continous sustainable molecular diagnostics of lung cancer rational algorythms, affordable technology and appropriate reimbursement are equally necessary.